Dragman : a novel - Appleby, Steven (Metropolitan Books/Henry Holt and Company, 2020)
"August Crimp can fly, but only when he wears women's clothes. Soaring above a gorgeous, lush vista of London, he is Dragman, catching falling persons, lost souls, and the odd stranded cat. After he's rejected by the superhero establishment, where masked men chase endorsement deals rather than criminals, August quietly packs up his dress and cosmetics and retreats to normalcy - a wife and son who know nothing of his exploits or inclinations. When a technological innovation allows people to sell their souls, they do so in droves, turning empty, cruel, and hopeless, driven to throw themselves off planes. August is terrified of being outed, but feels compelled to bring back Dragman when Cherry, his young neighbor, begs him to save her parents. Can Dragman take down the forces behind this dreadful new black market? Can August embrace Dragman and step out of the shadows? The debut graphic novel from British cartoon phenomenon Steven Appleby, Dragman is at once a work of artistic brilliance, sly wit, and poignant humanity, a meditation on identity, morality, and desire, delivered with levity and grace"--